Why was the participation of Indian states in the growth turnaround so patchy? Some evidence based on robustness analysis - Chetan Ghate; Stephen Wright (Indian Council for Research on International Economic Relations (ICRIER), 2012)
In Ghate & Wright Journal of Development Economics, vol. 99 (2012) pp 58-67, we noted that there was considerable variation in the extent to which different Indian states participated in the Great Indian Growth Turnaround. In this paper we investigate whether there was any systematic relationship between participation in the turnaround and the characteristics of Indian states, using the robustness approach originally proposed by Sali-i-Martin (1997). We supplement our robustness analysis by asking whether more recent (post-sample) experience is consistent with our results.
Keywords: O10; O40; O53; O47; 330; Indian Economic Growth; Convergence; Divergence; Growth Regressions; Common Factors; Regionales Wachstum; Regionalentwicklung; Wirtschaftliche Konvergenz; Robustes Verfahren; Teilstaat; Indien